TRANSLATION SHIFT IN CHILDREN’S LITERATURE: A CASE STUDY OF A TALE OF TWO SISTERS - Chyntia Farah Agustine; Afifahtur Rachmadina; Muhammad adani Maulidan; Ruri Fadhilah Kurniati (ETNOLINGUAL, 2026)
This study explores the use of translation shifts in the bilingual children's book A Tale of Two Sisters and its Indonesian version Kisah Dua Saudara. The research aims to identify the types of category shifts applied in the translation process and explain how these shifts help maintain meaning, clarity, and natural flow between English and Indonesian. Using a descriptive qualitative approach, the data were taken from English–Indonesian sentence pairs and analyzed using Catford’s theory of translation shifts. The analysis reveals four types of category shifts: structure shifts, class shifts, unit shifts, and intra-system shifts. Among them, structure shift was the most frequently used, often seen in the rearrangement of grammatical patterns to fit Indonesian sentence structure. Class shifts appeared when word classes, such as adjectives and verbs, were changed to suit the context. Unit shifts occurred when larger grammatical units like clauses were translated into shorter phrases or single words. Intra-system shifts reflected differences in plural forms, articles, and possessives between the two languages. These shifts are not errors, but necessary adjustments that help preserve the original meaning while making the text sound natural and understandable in the target language. The findings show that translation shifts are essential tools for translators, especially when working with literary texts aimed at young readers, where clarity, simplicity, and grammatical accuracy are key to effective communication.